Pendidikan Akhlak Peserta Didik dan Pendidik Dalam Perspektif Hadis Nabi - Fauziyah, Nur Laily (STIT Al-Marhalah Al-Ulya Bekasi, 2018)
Morality is a trait attached to a person and becomes his identity. Noble character is the main foundation in the formation of a perfect Muslim. In order to form a noble person, it is very important to do an early effort in building the values of noble morals, including through education. However, it is not easy to instill good morals through education. There are a number of problems encountered, namely the lack of teacher exemplary (educator); school atmosphere that is not conducive; schools are less than optimal in the actualization of morals; diverse student characters who come from diverse families; lack of communication between parents of students and schools (institutions); and the negative impact of the current modernization which is increasingly unstoppable. In this case Rasulullah SAW through some of the hadith gives a picture of morals that should be applied by educators and students in everyday life, such as; respect for educators and students, good manners in the majlis of science, being gentle and so on. The implementation of moral values can be done with the method of habituation, giving examples (daily practice), direct advice as well as criticism or satire subtly into all relevant subjects especially in religious education and citizenship, integrating moral education into activities that are programmed or planned, establishing communication or collaboration between educational institutions and parents of students, and optimizing the role models of educators.